Back-end performance - Škvorc, Bruno (SitePoint Pty. Ltd., 2017)
Performance simply matters. Technology may allow us to "go bigger", but maybe not necessarily be better when it comes to performance. Now is the time to utilize the amazing tools that are available for making websites faster, and to learn how to improve user experience and satisfaction. This is a practical collection of tutorials on back-end website performance for web developers. It's packed with useful, real world hints and tips that you can use on your sites today. It contains: How to Optimize MySQL: Indexes, Slow Queries, Configuration by Bruno Skvorc How to Read Big Files with PHP (Without Killing Your Server) by Chris Pitt WordPress Optimization by Tonino Jankov HTTP/2: Background, Performance Benefits and Implementations by Tonino Jankov Apache vs Nginx Performance: Optimization Techniques by Tonino Jankov An In-depth Walkthrough of Supercharging Apps with Blackfire by Reza Lavaryan How to Boost Your Server Performance with Varnish by Tonino Jankov How to Process Server Logs by Daniel Berman This book is for all back-end developers who wish to build sites and apps that are more performant. You'll need to be familiar with server-side development in order to follow the discussion.